(untitled) (Iraqi Journal of Medical Sciences, 2023)
Background: The increasing rate of births through caesarean sections (CS) had become a source of concern in many countries. Maternal beliefs may influence the mode of delivery. Knowledge of pregnant women regarding CS and its complications is an important tool to assess their choice for birth modality. Objective: To assess women knowledge toward complications of CS and to find out the relationship between level of knowledge and their demographic characteristics. Methods: A cross sectional study with analytic elements was conducted in Baghdad Teaching Hospital, Medical City Complex in 2022 on women visited Gynecology and Obstetrics Consultation Outpatient Clinics and Ward for different reasons. Results: The study included 400 women, 67.5% (270) aged